Praças de estacionamentos como estratégia para melhoria no trânsito de áreas centrais - Mendes, Flávia Bruno (2010)
The traffic problems are of general scope in several cities in the world, especially in central area, usually more congested. This work aims to simulate an operational alternative that provides improved flow of vehicles in the central area. It is proposed the elimination of parking lots regulated rotary (called Blue Zone ) on the streets and main avenues in the downtown area and meeting this need with the implementation of parking garages/lots in buildings and / or underground garages in places near the central area. Identify the best location for such a development strategy includes facility location approach to logistics and optimization of the distance pathway. It can be pointed out urban politics for Land Use and Transportation, urban planning and needs applied to determine strategic locations for new enterprises considering the logistics. Some strategies of traffic management adopted in Brazil, United States and Europe are generally discussed with their benefits and limitations. The strategic locations were selected considering Clustering and Facility Location approaches using software TransCAD. Reduction of blue zones allows increasing the capacity of lane and therefore, improving the performance in central area. This benefit can be measured through the simulation, using Traffic Software Integrated System, taking into account Traffic Engineering. That is the case of downtown in Uberlandia. Comparing the proposed and real scenario it could be reduced delay and waiting time, fuel consumption and greenhouse gas emissions. The results pointed the better scenario of the central area and also showed it is important to review the land use/transportation. It is necessary to adopt integrated politics to improve the performance of the routes due the increased flow vehicles and traffic problems. The relocation of parking lots is a current alternative which improves the vehicles flow and the mobility in downtown.